Dobre in slabe izkušnje z dopuščeno revizijo po ZPP - Dolenc, Mile (Podjetje in delo, 2015)
The new regulation of the appeal on points of law, which introduced the leave to appeal, has certainly fulfilled essential expectations, namely, the reduction of excessive workload of the Supreme Court of the Republic of Slovenia. However, there are some drawbacks. One of these is that the Supreme Court has to decide on the leave to appeal without a file. That is the reason for an occasional lack of sufficient information for the ruling. There is also a need for modernization of procedure before the Supreme Court, including the introduction of oral hearing.
Keywords: revizija; sodišča; sodne odločbe; sodni postopek; vrhovna sodišča